Environmental Performance of Retail Trade Companies in Russia - BRAGIN, Leonid Aleksandrovich; IVANOV, Gennady Gennadjevich; MAYOROVA, Albina Nikolaevna; MAYOROVA, Elena Aleksandrovna; NIKISHIN, Alexander Fedorovich (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018, 2018)
An important condition for a sustainable and balanced development of the Russian economy is to increase the environmental performance of commercial companies, including trade ones. The purpose of the study is to assess the environmental performance of retail trade companies operating in the Russian Federation. The index, calculated based on the data included in their annual reports, taking into account thirteen parameters characterizing various environmental aspects of trading activity, is used to assess the environmental performance of retail trade companies. The results obtained have made it possible to draw the following conclusions: first, in recent years, the environmental performance of Russian retail trade companies has shown the upward trend; secondly, the environmental performance of foreign retail trade companies operating in the Russian Federation is higher than the environmental performance of Russian companies. Despite the positive dynamics, the problem of increasing the environmental performance of retail trade companies remains of significant importance both for individual economic entities and for the entire state. A further increase in the environmental performance of retail trade companies will improve their competitiveness and the resulting social and economic performance, and will also contribute to the formation of a balanced, environmentally oriented model for the development of the Russian economy.